Quality and readability of online health information on menopausal hormone therapy in Canada: what are our patients reading?. Issue 1 (January 2022) - Murtaza, Fahmeeda; Shirreff, Lindsay; Huang, Lina N.; Jacobson, Michelle; Jarcevic, Radomir; Christakis, Marie K.
Abstract: Objective: To assess the quality and readability of 24 of the most accessed menopause hormone therapy (MHT) websites by Canadian women. Methods: The top 24 websites from Google, Bing, and Yahoo were identified using the search term "hormone replacement therapy." Five menopause specialists assessed website content quality using the DISCERN Instrument, Journal of the American Medical Association (JAMA) benchmarks, and Abbott's Scale. Two reviewers assessed website credibility using the Health on the Net Foundation Code of Conduct certification, and website readability using the Simple Measure of Gobbledygook, Flesch-Kincaid Grade Level, and Flesch-Kincaid Read Ease formulae. Results: Scores for quality of information varied. The mean JAMA score was low at 2.3 ± 1.1 (out of 4). Only one website met all benchmarks. Fourteen websites (58%) had a good/excellent DISCERN score, while four (17%) had a poor/very poor score. For Abbott's Scale, both the mean authorship score at 2.2 ± 1.0 (out of 4) and mean content score at 45.9 ± 9.8 (out of 100) were low. Inter-rater reliability was high for all tools. Fifteen websites (63%) were Health on the Net Foundation Code of Conduct certified. The mean Flesch-Kincaid Read Ease was 42.7 ± 10.3, mean Flesch-Kincaid Grade Level was 12.3 ± 1.9, and mean Simple Measure of Gobbledygook grade level was 11.3 ± 1.5. Only one website presented content at a reading level recommended for the public. Websites meeting more JAMA benchmarks were significantly less readable ( P  < 0.05). Conclusion: Although good quality MHT information exists online, several resources are inaccurate or incomplete. Overall, these resources are not considered comprehensible by the public. There is a need to disseminate accurate, comprehensive, and understandable MHT information online. Abstract : Supplemental Digital Content is available in the text